1999
DOI: 10.1046/j.1365-2222.1999.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term preseasonal birch pollen allergoid immunotherapy influences symptoms, specific nasal provocation and cytokine levels in nasal secretions, but not peripheral T‐cell responses, in patients with allergic rhinitis

Abstract: It was possible to evaluate 27 patients in accordance with the study protocol. Clinical symptoms and medication intake were reduced as a result of the IT as were nasal secretion levels of IL-5 (P = 0.007). IFNgamma was increased in nasal secretions (P = 0.01), while IL-4 was not measurable in most samples. No effect was found on proliferation of birch pollen-reactive TCLs, cytokine production by TCLs and the frequency and ratio of CD4+ and CD8bright or CD45RA+ and CD45RO+ cells in peripheral blood (all P > 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 41 publications
5
43
0
Order By: Relevance
“…All these molecules exhibit a decreased binding capacity for IgEs, and are shown following intradermal injection to display a lower reactogenicity and a decreased capacity to release proinflammatory mediators and Th2 cytokines when compared to wild-type rBet v 1 [18]. While this approach should lead in theory to safe vaccines, there is as of today only limited proof of efficacy obtained in small cohorts of patients for nonnative allergens [37]. As a matter of fact, IgE binding might otherwise facilitate allergen capture and presentation by professional antigen-presenting cells such as dendritic cells and activated B lymphocytes, which are known to express both high and low affinity (Fc ε RI and CD23) [38, 39]surface receptors for IgE, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…All these molecules exhibit a decreased binding capacity for IgEs, and are shown following intradermal injection to display a lower reactogenicity and a decreased capacity to release proinflammatory mediators and Th2 cytokines when compared to wild-type rBet v 1 [18]. While this approach should lead in theory to safe vaccines, there is as of today only limited proof of efficacy obtained in small cohorts of patients for nonnative allergens [37]. As a matter of fact, IgE binding might otherwise facilitate allergen capture and presentation by professional antigen-presenting cells such as dendritic cells and activated B lymphocytes, which are known to express both high and low affinity (Fc ε RI and CD23) [38, 39]surface receptors for IgE, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A shift of the cytokine profile toward Th1 during treatment with an OVA allergoid was shown in mice (4). In humans effective allergoid therapy was evident by significant reduction of the IL-5 production in nasal secretions accompanied by increased IFN-␥ production (13), indicating the involvement of T cells in this beneficial effect.…”
mentioning
confidence: 96%
“…Both, a shift toward Th1, 71,72 as well as an unchanged Th1/Th2-ratio, [73][74][75] was observed. However, cultures of PBMCs do not provide accurate insights into immune responses of affected organs and associated lymphoid tissue.…”
Section: Discussionmentioning
confidence: 91%
“…An increased Th1/Th2 ratio, with mostly unchanged Th2 but increased Th1 cytokines (IL-2, IFN-g and IL-12) was demonstrated in skin biopsy upon intradermal challenge after grass pollen SIT, 76 in mucosal biopsy upon intranasal provocation after pollen SIT, 77 and in nasal biopsies and nasal fluids in response to natural pollen exposure in patients after pollen SIT. 73,75 However, these studies demonstrated the change of whole T cells in the tissues and due to technical problems could not focus on allergen-specific T cell subsets.…”
Section: Discussionmentioning
confidence: 99%